Justiça e paz com a criação : a ecologia em interação com justiça e paz na experiência prática e reflexiva do Conselho Mundial de Igrejas - Pereira, Pilato (2012)
Since the globalization advent of a world of time change, we envision a climate of injustice, in which the life created by God is despised in favor of profit. In a time marked by carelessness and threat of scarcity and privatization of the natural resources, humanity and Earth feel the drama of climate changes. Therefore, it has been time of wondering about faith in God the Creator. What do the Christian Churches state and do and/or what could/should they say and do in face of environmental issues? Then, with that concern, we devoted to research the ecotheology of the World Council of Churches (WCC). This research has as argument the practical and reflexive experience of WCC about the interaction of ecology with justice and peace since the world ecumenical call of Seul in 1990. We also seek to do a counterpoint with the ecotheology by Leonardo Boff and the experience of the Ecology Pastoral of CNBB Sul 3. Moreover, following the logic of the see-judge-act method, this dissertation intends to demonstrate the transversality of ecology of the world ecumenical movement connected to WCC. This study is focused on the document of the Justice, Diakonia and Responsibility with Creation program, more specifically the Eco-Justice project of the Commission of the Churches on International Affairs of WCC. Eco-Justice is the consonance of a long tradition of WCC in approaching the transversal relations among Justice, Peace and Integrity of Creation. WCC makes a Bible rereading and, under an ecological light, with an attentive perceiving of both Earth and poverty prophecy, has been calling churches to reassume their alliance of justice, love and peace with God the Creator and the Defender of Life.